Avatar, the last airbender. The complete book 2 collection [videorecording (DVD)] = Jiang shi shen tong - DiMartino, Michael Dante; Konietzko, Bryan (Paramount Pictures, 2007)
Avatar Aang continues his quest to master the four elements before the end of summer. Together with Katara, Sokka, Momo, and Appa, he journeys across the Earth Kingdom in search of an Earthbending mentor. Along the way, he confronts Princess Azula, treacherous daughter of Firelord Ozai and sister to Prince Zuko. More powerful than her brother, Azula will stop at nothing to defeat the Avatar. But Aang and the gang find plenty of Earth Kingdom allies to help them along the way. From the swamps of the South to the Earth King's palace, Avatar: Book 2 is an adventure like no other.